Assessing Vulnerability in Households and Communities Involved in Fisheries Sector Activities - Taves, Jessica Rebecca (Université d'Ottawa / University of Ottawa, 2015)
Global fisheries are in decline in response to intense pressure to feed a growing world population. Many of the world’s fisherpeople live in poverty and suffer disproportionately from this threat to global fish stocks due to competition for resources among other stressors. In recent years the Vietnamese government has encouraged small-scale aquaculture production for economic development and to mitigate declining fisheries livelihoods. Using data from the 2013 Vietnam Transitions Survey this paper examines different measures of household vulnerability to the declining fishery and the resulting uncertain economic future. Analysis reveals that the most vulnerable group among survey participants are those who depend primarily on extensive aquaculture for their household income. Despite the frequency of disease in fish, intensive aquaculture remains an attractive livelihood activity. Households are theoretically willing to face increased risk in exchange for greater prosperity, but are typically unable to do so due to cost-related barriers to entry.
Keywords: Fisheries; Aquaculture; Vulnerability; Vietnam; Development; Livelihoods